Fluoride content of bottled drinking waters available in Riyadh, Saudi Arabia - Abdullah M. Aldrees; Saad M. Al-Manea (Saudi Dental Journal)
Aims: This study aimed to examine the fluoride concentration of commercially available bottled water products in Riyadh, Saudi Arabia, and to assess the accuracy of the labeling of fluoride concentration on the tested brands. Methods: Fifteen randomly selected commercial brands of bottled water were obtained from supermarkets in Riyadh, Saudi Arabia. Three bottles of each brand were purchased, and fluoride content was measured using a combination fluoride-ion-selective electrode. The average reading for each brand was estimated and also compared with the fluoride content printed on the label. Results: The mean (±SD) fluoride content of the 12 local bottled water samples was 0.79 (±0.09) mg/L with a range from 0.5 to 0.83 mg/L. The mean fluoride concentration of the three imported brands was 0.67 (±0.02) mg/L with a narrow range of fluoride content (0.65–0.69). All tested samples mention the fluoride content on the label except two imported brands. Five samples showed a significant difference between our evaluation and stated content of fluoride that ranged between +0.46 and −0.2 mg/L. Conclusions: Bottled drinking waters available in Riyadh, Saudi Arabia contain differing concentration of fluoride, but within a safe range for use as a source of systemic fluoride. In addition, the manufactures’ labeling of fluoride content may be inaccurate. Keywords: Bottled water, Fluoride, Riyadh, Saudi Arabia